Operando Raman characterization of unique electroinduced molecular tautomerization in zero-gap electrolyzers promotes CO 2 reduction - Ling Li; Wentao Ye; Qiliang Liu; Ruoxi Liu; Xingyu Lu; Tianbing Yao; Linqin Wang; Bing Gu; Licheng Sun; Wenxing Yang (Proceedings of the National Academy of Sciences, 2025)
Membrane electrode assembly (MEA) represents an advanced type of electrochemical device currently widely used in various electrocatalysis applications [e.g., electrochemical CO 2 reduction reaction (CO 2 RR)], featuring no explicit catholyte flow and a unique “solid–liquid–gas” triple-phase interface. Herein, we identify a peculiar electroinduced thiol to thione tautomerization of 4-mercaptopyridine (4MPy) molecule on Cu catalyst surfaces at this triple-phase interface driven by cathodic polarization. This leads to a significant performance improvement of CO 2 RR on Cu with a C 2+ Faradaic efficiency of over 80% with more than 60% C 2 H 4 , as well as a 300 mV reduction of cell voltage compared to bare Cu. A home-designed MEA-type operando Raman cell enables mechanistic studies directly under a current density of over 100 mA cm −2 , elucidating the intricate impacts of the 4MPy tautomerization on the local catalytic environments under real reaction conditions. Surprisingly, this tautomerization does not occur in other commonly utilized electrolyzers, e.g., flow cell and H-cell, even with the same catalyst and electrolyte conditions. The direct contact with the electrolyte in the latter cells was found to cause rapid desorption of 4MPy from the catalyst surface before its possible chemical transformation. These results highlight the opportunities of utilizing surface molecular tautomerization to promote CO 2 RR performance and using the triple phase of MEA to drive reactions that would otherwise be hard to happen in classical electrochemical devices of similar conditions.